Laser and GTAW torch processing of Fe–Cr–B coatings on steel. (October 2014) - Md Idriss, A. N.; Mridha, S.; Baker, T. N.
<x content-type="archive" xml:space="preserve">Abstract</x> A comparison of a coating of Fe–Cr–B alloy powder processed on a plain carbon steel by surface melting using either laser or gas tungsten arc welding (GTAW) torch was made. The alloy powder was injected in laser melted surface, while the preplaced powder was melted using the GTAW technique. The topography of the GTAW tracks showed a relatively smooth surface, but the laser track surface was very rough. Because of high energy input, the GTAW method produced very wide and deep tracks with a high dilution compared to those of the laser tracks. Pores and fine cracks were seen in laser tracks; the cracks were elongated across the track width, and some of them propagated down to the melt depth. The GTAW track produced at a low energy was free from any cracking, but a centreline crack was present when processed at a high energy input.